Effect of Feeding High Proportion Concentrates Containing Tofu Waste on Nutrient Consumption, Milk Production, Body Condition Score and Postpartum Mating Period of Dairy Goats in Yogyakarta, Indonesia - Suranindyah, Yustina Yuni; Rochijan; Adiarto; Widyobroto, Budi Prasetyo; Astuti, Sulvia Dwi; Murti, Tridjoko Wisnu (Pakistan Journal of Nutrition, 2018)
Objective: This study was conducted to investigate the effect of feeding a high proportion concentrate containing tofu waste on nutrient consumption, milk production, body condition (BC) score and length of postpartum mating (PPM) period of dairy goats. Methodology: Data were collected from 30 lactating goats on small farms in the Sleman region of the Yogyakarta province in Indonesia. The goats were fed diets consisting of Calliandra calothyrsus and wheat pollard with (Farm B, Diet B) or without (Farm A, Diet A) tofu waste. The proportion of concentrates in the diets on a dry matter (DM) basis was 20 and 55% for Diet A and Diet B, respectively. Data for feed and nutrient consumption, milk production, BC score and length of PPM period were collected. All data were statistically analyzed by t-test. Results: Feeding a high proportion concentrate containing tofu waste significantly (p